Hepatitis B virus infection in patients presenting for immunosuppressive cancer therapy with and without underlying HIV infection - Ngoato, Malowane H.; Amponsah-Dacosta, Edina; Blose, Ntombifuthi; Selabe, Selokela G.; Msibi, Thembeni L.; Motswaledi, Mojakgomo H.; Musyoki, Andrew M. (Frontiers in Virology, 2023)
Reactivation of hepatitis B virus (HBV) infection induced by immunosuppressive cancer therapy is associated with fulminant liver disease and death. While national guidelines recommend HBV screening and antiviral prophylaxis for patients with cancer prior to initiating immunosuppressive therapy, compliance with these measures is unclear. This study characterized the burden of HBV infection among patients diagnosed with gynaecological or dermatological cancers, with or without underlying HIV infection, before initiating immunosuppressive therapy. Between 2016–2018, we recruited study patients from the Dr George Mukhari Academic Hospital in Tshwane, South Africa. Demographic (age, sex) and clinical data (HIV test results, HIV antiviral regimen, type of cancer) were recorded using a standardized data collection form. All participants were tested for HBV surface antigen (HBsAg), and antibodies to the surface (anti-HBs) and core antigens (anti-HBc). For detection of HBV DNA, a nested polymerase chain reaction was used to amplify polymerase gene fragments which were Sanger-sequenced and analyzed using bioinformatics software. All statistical analyses were performed using R version4.1.0 (2021-05-18) and R studio version 2022.07.2. Study participants were predominantly female (96.3%, 103/107) with a median (IQR) age of 50 (17.5) years. Cervical cancer was the most frequent cancer diagnosis (72%). Over half (52.3%; 56/107) of the participants were HIV positive and all but four (92.9%) on highly active antiretroviral therapy at the time of enrollment. The prevalence of chronic hepatitis B in the study population was 11.2% [95% CI:6.2-19.1], increasing to 14.3% [95% CI:6.8-26.8] in the HIV positive sub-population. The overall prevalence of occult HBV infection was 20% [95% CI:12.8-29.7], 57.9% [95% CI:33.97-78.9] of whom tested negative for all serological markers. Phylogenetic inference showed that all polymerase gene sequences generated in this study were sub-genotype A2. Mutational analysis did not reveal any drug resistance-associated amino acid variations in this study. These findings suggest that chronic and occult HBV infections are more prevalent among cancer patients with or without underlying HIV infection compared to what has previously been reported for the general South African population. This underscores the need to scale-up universal HBV serological and molecular screening with timely institution of prophylaxis prior to initiating immunosuppressive cancer therapy.